(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
This study investigates the histomorphological alterations in the gastric mucosa induced by chronic low-dose exposure to carbon monoxide (CO), as well as the potential corrective effects of asparagus (Asparagus officinalis) oil. Experimental findings revealed that CO toxicity caused epithelial dystrophy, reduced gland density, and increased stromal collagenization. Administration of asparagus oil, rich in antioxidant and non-protein-binding bioactive compounds, supported tissue regeneration, restoring up to 85–90% of mucosal structure integrity. These results suggest the effectiveness of asparagus oil as a promising gastroprotective agent against CO-induced damage.